A Quantitative Study Assessment of Public Knowledge Regarding Self-Medication with Ibuprofen In Marang Kayu District: A Quantitative Study - Triswanto Sentat; Ika Nurjannah; Siti Jubaidah; Heri Wijaya; Rusdiati Helmidanora (JSFK (Jurnal Sains Farmasi & Klinis), 2025)
Self-medication is an approach widely used by the public to treat mild pain symptom by using over-the-counter medications without a prescription from physician. One of the medications that can be used for self-medication is Ibuprofen. Ibuprofen is a drug that can be used for self-medication; however, its use should be under the supervision and guidance of healthcare professionals. This study aims to determine the level of public knowledge regarding the self-medication use of ibuprofen in Marang Kayu District. This research uses a quantitative design with a descriptive approach. Data were collected through questionnaires distributed to 369 respondents selected using purposive sampling. The questionnaire included questions about knowledge aspects regarding ibuprofen and self-medication patterns. The study results showed that the level of public knowledge in Marang Kayu District about Ibuprofen for self-medication was 14.5% (49 respondents) with a high level of knowledge, 31.3% (106 respondents) with a moderate level of knowledge, and the majority, 54.3% (184 respondents), with a low level of knowledge. The results underscore the urgent need for targeted health education programs to improve public awareness and promote safe self-medication practices. Enhancing community knowledge is essential to minimize the risks associated with improper ibuprofen use and to encourage responsible drug consumption